Multi-joint actuation platform for lower extremity soft exosuits - Ye Ding; Galiana, Ignacio; Asbeck, Alan; Quinlivan, Brendan; De Rossi, Stefano Marco Maria; Walsh, Conor (Proceedings - IEEE International Conference on Robotics and Automation, 2014)
Lower-limb wearable robots have been proposed as a means to augment or assist the wearer's natural performance, in particular, in the military and medical field. Previous research studies on human-robot interaction and biomechanics have largely been performed with rigid exoskeletons that add significant inertia to the lower extremities and provide constraints to the wearer's natural kinematics in both actuated and non-actuated degrees of freedom. Actuated lightweight soft exosuits minimize these effects and provide a unique opportunity to study human-robot interaction in wearable systems without affecting the subjects underlying natural dynamics. In this paper, we present the design and control of a reconfigurable multi-joint actuation platform that can provide biologically realistic torques to ankle, knee, and hip joints through lower extremity soft exosuits. Two different soft exosuits have been designed to deliver assistive forces through Bowden cable transmission to the ankle and hip joints. Through human subject experiments, it is demonstrated that with a real-time admittance controller, accurate force profile tracking can be achieved during walking. The average energy delivered to the test subject was calculated while walking at 1.25 m/s and actuated with 15% of the total torque required by the biological joints. The results show that the ankle joint received an average of 3.02J during plantar flexion and that the hip joint received 1.67J during flexion each gait cycle. The efficiency of the described suit and controller in transferring energy to the human biological joints is 70% for the ankle and 48% for the hip.